Effects of antiepileptic drugs on thyroid hormone function in epilepsy patients. (May 2017) - Shih, Fu-Yuan; Chuang, Yao-Chung; Chuang, Ming-Jung; Lu, Yan-Ting; Tsai, Wan-Chen; Fu, Ting-Ying; Tsai, Meng-Han
Highlights: 17.4% epilepsy patients had low fT4. Female patients with epilepsy and an older age, AED polytherapy, and carbamazepine treatment had a higher risk of low fT4. Thyroid function in elderly female epilepsy patients who received carbamazepine therapy should be monitored. Abstract: Purpose: Patients with epilepsy are frequently required to take antiepileptic drugs (AEDs) for a long period of time. Many studies have shown that AEDs have a negative influence on endocrine function including the thyroid gland, however the risk factors for the development of low thyroid function in these patients are unclear. This study aimed to determine the potential risk factors of low thyroid function in patients with epilepsy. Method: This was a cross-sectional study including 298 patients with epilepsy. Patients with previous thyroid disease were excluded. Epidemiologic data, type of epilepsy, etiology, the age of seizure onset, duration of epilepsy, intractable epilepsy, and number and dosage of AEDs were recorded. Levels of free thyroxine (fT4) and thyroid stimulating hormone (TSH) were measured.Results: Fifty-two of the 298 (17.4%) patients had low fT4. Older age ( P = 0.004), female sex ( P = 0.014), longer duration of epilepsy ( P = 0.001), and intractable epilepsy ( P = 0.009) were significantly associated with low fT4. Regarding individual AEDs, carbamazepine (30.1%), topiramate (28.6%), and levetiracetam (24.3%) were significantly associated with the presence of low fT4. After stepwise logistic regression of all significant variables, female sex, older age, three or more AEDs, and carbamazepine were independent risk factors for low fT4. Conclusions: Female patients with epilepsy and an older age, AED polytherapy, and carbamazepine treatment had a higher risk of low fT4. Thyroid function in these patients should be monitored closely.